2021
DOI: 10.1111/cid.13044
|View full text |Cite
|
Sign up to set email alerts
|

Effect of customized healing abutments on the peri‐implant linear and volumetric tissue changes at maxillary immediate implant sites: A 1‐year prospective randomized clinical trial

Abstract: Background: Immediate implant placement (IIP) associated with the use of bone substitutes and collagen matrices (CM) seems to reduce the amount of resorption at peri-implant areas. Recently, customized healing abutments (CA) appeared as another solution in order to seal the socket and preserve the original soft tissue contour.Purpose: To evaluate peri-implant tissues dimensional changes after using customized healing abutments compared with the use of xenogeneic collagen matrices as socket sealing options in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1
7

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 44 publications
2
14
1
7
Order By: Relevance
“…An RCT from Perez et al (2020), comparing customized healing abutments and standard healing abutments at IIP sites, showed favorable results in terms of papilla presence and marginal bone loss at the sites treated with customized abutments. Fernandes et al (2021) also noticed statistically significant less volume variation at the first‐month follow‐up after the use of a customized healing abutment when compared to a collagen matrix as socket sealing option in IIP, although after the 1‐year follow‐up, no significant differences were found. It must be highlighted that in the control group, it was used a matrix that will clearly influence the healing cascade and enhance re‐epithelialization.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…An RCT from Perez et al (2020), comparing customized healing abutments and standard healing abutments at IIP sites, showed favorable results in terms of papilla presence and marginal bone loss at the sites treated with customized abutments. Fernandes et al (2021) also noticed statistically significant less volume variation at the first‐month follow‐up after the use of a customized healing abutment when compared to a collagen matrix as socket sealing option in IIP, although after the 1‐year follow‐up, no significant differences were found. It must be highlighted that in the control group, it was used a matrix that will clearly influence the healing cascade and enhance re‐epithelialization.…”
Section: Discussionmentioning
confidence: 94%
“…Over the years, numerous surgical and prosthetic techniques have been elaborated to avoid possible IIP future complications (Blanco et al). The preference for surgical procedures such as a flapless atraumatic approach and a palatal positioning of the implant (Raes et al, 2011), the filling of the gap between the implant shoulder and the bone walls with deproteinized bovine bone mineral (DBBM) (Zaki et al, 2021), the use of a customized healing abutment (Fernandes et al, 2021), and the application of an autologous connective tissue graft (CTG) (Seyssens et al;Raghoebar et al, 2021) seem to counteract the shrinkage at the peri-implant area. Several studies' analyses have shown advantages of harvesting a CTG for buccal volume augmentation, reporting less midfacial recession, and a wider and thicker gingival biotype (Migliorati et al, 2015;Zuiderveld et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants aged >18 years were selected from potential candidates having nonrestorable single teeth in the esthetic zone (maxillary teeth up to second premolars) and bounded by adjacent periodontally intact teeth. Eligibility criteria included the presence of labial/buccal bone deficiency of 50% or more or the total height with intact overlying soft tissues, 17–19 a thick biotype assessed through probe transparency 20 and at least 2 mm of keratinized mucosa band apical to the mid‐facial soft tissue margin, in addition to the presence of adequate apical bone to the extracted root to engage the dental implant 21,22 . Exclusion criteria included the presence of acute signs of infection at the site of extraction, full mouth bleeding and plaque scores (FMBS and FMPS, respectively) >20% at time of surgery, current and past smoker (>5 years), females who are pregnant or expecting pregnancy during the study period, presence of systemic conditions that contra‐indicate elective surgery or may affect surgical site healing (e.g., uncontrolled diabetes, metabolic bone diseases, or associated medications) and a recent history of radiotherapy or chemotherapy 23 .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the CAD/CAM fabrication involves additional steps and costs. Another approach is the use of prefabricated metrics 21 . More recently, several implant manufactures introduced automatic profile generator which is a 3D printed silicone index that can be used to make custom healing abutments of different sizes and emergence profiles corresponding to each extracted tooth.…”
Section: Introductionmentioning
confidence: 99%